Nourishing the nation : food as national identity in Catalonia - Johannes, Venetia (New York : Berghahn, 2020)
"In the early twenty-first century, nationalism has seen a surprising resurgence across the Western world. In the Catalan Autonomous Community in northeastern Spain, this resurgence has been most apparent in widespread support for Catalonia's pro-independence movement, and the popular assertion of Catalan symbols, culture and identity in everyday life. Nourishing the Nation provides an ethnographic account of the everyday experience of national identity in Catalonia, using an essential, everyday object of consumption: food. As a crucial element of Catalan cultural life, a focus on food provides unique insight into the lived realities of Catalan nationalism, and how Catalans experience and express their national identity today"--
Introduction. Nourishing Catalan nationalism -- Catalan cookbooks : creating Catalonia through culinary literature -- The foundational sauces and national dishes -- Catalan cuisine in context -- The gastronomic calendar : seasonality, festivity and territory -- Catalan national days and their foods -- Conclusion. Cuisine as national identity.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on January 17, 2020).
JSTOR
Keywords: Food habits -- Political aspects -- Spain -- Catalonia; Food habits -- Social aspects -- Spain -- Catalonia; Cooking, Spanish -- Catalonian style -- Social aspects; National characteristics, Catalan; Nationalism -- Spain -- Catalonia; Catalonia (Spain) -- History -- Autonomy and independence movements; Habitudes alimentaires -- Aspect politique -- Espagne -- Catalogne; Habitudes alimentaires -- Aspect social -- Espagne -- Catalogne; Cuisine catalane -- Aspect social; Catalans; Nationalisme -- Espagne -- Catalogne; Catalogne (Espagne) -- Histoire -- Autonomie et mouvements indépendantistes.; SOCIAL SCIENCE / Agriculture & Food; Autonomy and independence movements; Food habits -- Social aspects; National characteristics, Catalan; Nationalism; Spain -- Catalonia; History